Direct seeded rice in Haryana (India) ABY districts: impact and lessons for scaling - Mutum, Lamnganbi; Mizan, Syed Adil; Bhatpuria, Dhyey; Taneja, Garima; Mitra, Archisman; Gupta, S. K.; Sikka, Alok (International Water Management Institute, 2025)
Rice is a staple crop in India, traditionally cultivated using the Transplanted Puddled Rice (TPR) method. This traditional method, while effective and very popular amongst farmers, is highly labour, water, and energy-intensive, that leads to significant groundwater depletion and higher energy usage in pumping groundwater. In response to these challenges, the Direct Seeded Rice (DSR) method has been introduced as a more sustainable alternative. DSR involves sowing seeds directly into the field, eliminating the need for growing and transplanting seedlings. This method, tested in various field trials, promises to have several benefits, including water savings, reduced labour and production costs, higher economic returns, and lower methane emissions. However, the success in farmer fields when adopted at scale outside trials remains to be analysed critically.